Surface reactivity of the natural metal (hydr)oxides in weathered tropical soils - Méndez Fernández, Juan Carlos (2021)
Assessing the surface reactivity of metal (hydr)oxides in soils is essential for quantifying ion adsorption phenomena that control the availability of nutrients and pollutants. Despite the high natural abundance of Fe and Al (hydr)oxides in intensively weathered environments, the surface reactivity of these pedogenic materials has not been consistently characterized for weathered tropical soils. Here, we used a novel probe-ion methodology combined with state-of-the-art surface complexation modelling (SCM) to derive the reactive surface area (RSA) of the soils, as well as the amount of phosphate (PO4) that can be potentially desorbed (R-PO4) from the natural fraction of metal (hydr)oxides and thereby controlling the solid-solution partitioning of PO4. We applied this methodology to a series of weathered topsoils from the sub-Saharan region. The results showed that nanocrystalline ferrihydrite (Fh) is a better proxy than well-crystallized goethite for describing with SCM the reactivity of the natural metal (hydr)oxides, even though well-crystallized materials dominate the mass fraction of metal (hydr)oxides of these weathered tropical soils. Using Fh as a proxy in the SCM, the RSA ranged from ∼2 to 40 m2 g−1 soil. Nanoparticles with a mean diameter of ∼1.5–5.0 nm dominate the reactive fraction of metal (hydr)oxides in these tropical topsoils. Our SCM in conjunction with soil extractions indicates that only a fraction of the total PO4 associated with the metal (hydr)oxides is reversibly adsorbed, whereas the majority of the total PO4 pool, on average ∼64%, is occluded in the crystalline Fe and Al (hydr)oxide fraction. Only this smaller reversibly adsorbed fraction is thus available for participating in sorption reactions that determine the solid-solution partitioning of PO4. Overall, this research provides new insights into the reactivity of the metal (hydr)oxide fraction in weathered tropical soils and highlights the relevance of these pedogenic materials in determining the speciation and availability of PO4.